Automatic X-Ray Film Viewer Based On Mega Arduino - Frisa Yugi Hermawan; Winda Wirasa; Atika Hendryani; Imam Setiawan (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
X-ray film is something that can not be separated in the world of radiology, in the form of large sheets and can only be seen using a film viewer. Film viewer, as a medium for clearly seeing X-ray films, often provides an excessive illumination dimension to the dimensions of the film you want to see. The purpose of this study is to create a film viewer module that automatically turns on the LED following the size of the film you want to put, capture images and save them at MMC. The method of this research is Arduino Mega based automatic film viewer design system. Colomn and row accuracy test results obtained a stable value, although tested using different X-ray film sizes with an accuracy level above 85%. The images captured by the camera are stored on MMC, formatted in the .JPG format and can be accessed for review. The conclusion in this study in the form of making an automatic X-Ray Film Viewer system has obtained the results beginning with the design of the Block diagram. Designing hardware and software that is done properly, can minimize errors and mismatches results in the manufacture and design of automatic X-Ray Film Viewer. The function test, which is carried out as a representation of the suitability of hardware and software design, is focused on the quality of the work to turn on the LED according to film size in rows and columns.